Constrained ICA and applications - Lu, Wei. (2008)
The thesis begins with proposing a unified approach to perform complete ICA, the uICA, for Blind Source Separation (BSS). Three major ICA algorithms are investigated and shown to fall into this approach. They differ only from the nonlinear functions used in the learning rules.